2021
DOI: 10.3389/fpsyg.2021.657858
|View full text |Cite
|
Sign up to set email alerts
|

International Comparative Study of Statistics Learning Trajectories Based on PISA Data on Cognitive Diagnostic Models

Abstract: The cognitive diagnosis model is an emerging evaluation theory. The mastery of fine-grained knowledge points of students can be obtained via the cognitive diagnostic model (CDM), which can subsequently describe the learning trajectory. The latter is a description of the learning progress of students in a specific area, through which teaching and learning can be linked. This research is based on nine statistical items in the Program for International Student Assessment (PISA) 2012 and an analysis of the respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…Learning trajectory can be obtained through continuous observation of individual learning processes or through quantitative research on many students’ tests ( Jia et al, 2021 ). The research in this field first started in the field of science and then gradually expanded to various disciplines.…”
Section: Research About Learning Trajectorymentioning
confidence: 99%
See 2 more Smart Citations
“…Learning trajectory can be obtained through continuous observation of individual learning processes or through quantitative research on many students’ tests ( Jia et al, 2021 ). The research in this field first started in the field of science and then gradually expanded to various disciplines.…”
Section: Research About Learning Trajectorymentioning
confidence: 99%
“…The result showed that students from Australia, Canada, the United Kingdom, and Russia shared similar main learning trajectories, whereas Finland and Japan were consistent with their main learning trajectories ( Wu et al, 2020 ). Subsequently, a study used the same method with PISA data to study learning trajectories in statistics ( Jia et al, 2021 ). These studies follow a similar line of thought but with improved methods.…”
Section: Research About Learning Trajectorymentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike traditional measurement models, which assume underlying low‐dimensional continuous latent traits, CDMs model students’ performance as a function of the multidimensional binary attribute mastery profile (α). There have been many successful CDM applications in educational assessment (e.g., Chang, 2012, 2015; Jia, Zhu, & Gao, 2021; Wu, Wu, Chang, Kong, & Zhang, 2020; Zhang & Wang, 2020). One of the simplest and most popular CDM models is the deterministic input, noisy ‘and’ gate (DINA) model (Henson, Templin, & Willse, 2009; Junker & Sijtsma, 2001).…”
Section: Theories In Educationmentioning
confidence: 99%
“…The G-DINA aims to measure to what extent students master a set of cognitive attributes (e.g., fractions, proportions, and decimals as a fine-grained cognitive mathematic attribute) to improve educational policy and practice. Some studies have already employed the G-DINA to analyze data from international comparative tests, such as PISA (Jia et al, 2021;Wu et al, 2020). However, before the G-DINA can be used on international assessments to perform the CDA, a content analysis of the test must occur (von Davier & Lee, 2019).…”
mentioning
confidence: 99%